PENDIDIKAN KIMIA BAHAN MAKANAN UNTUK MEMBANGUN KESADARAN MAKAN MAKANAN SEHAT - Familia Novita Simanjuntak (Jurnal Dinamika Pendidikan, 2015)
"Men sana in corpore sano", strong soul stays within a healthy body. This slogan is firmly attached inside the mindset of the parents who constantly strive to run a healthy lifestyle by eating healthy foods. But now, in the era of modern and fast-paced, food technology developments offer a great selection of processed food products that are attractive and fast to the public without considering the nutrients needed by the human body. In fact, the number of food product advertisement serve the interesting and am-biguous packaging information which impact on consumption patterns that are not based on awareness of eating. Awareness of eating can be formed by the knowledge of the characteristics of all types of daily food. Food chemistry education is one of the right ways to complement public knowledge about the characteristics of all types of daily food, especially about the best nutrients of food needed to maintain his physical and mental health. Finally, when the awareness of healthy foods eating that has been formed and embedded in society as a whole, then it would have a positive impact on the development of a healthy and strong Nation.Keywords : food chemistry education, awareness of eating